O nowy model prawa pracy - Szubert, Wacław (Wydział Prawa i Administracji UAM, 1988)
The article is devoted to the presentation of some most important elements of a new model of the labour law. First, the author shows the contrasts between the situation which existed before and after 1980 in the sphere of the labour law and labour relations. Next, he formulates some postulates concerning the future shape of the labour law. He indicates that the pre-1980 model was of etatistic and centraliste character where the employers were the extension of the State and the protection of the employees' interests could not be adequate since on the one hand the law regulating the employment relations was formed exclusively by the State organs and on the other the trade unions, being a part of the State structure, did not represent the employees' interests properly. After 1980 some new forms of relations between the State and the employees appeared: social agreements and negotiations. Moreover, the Act of 1981 on State Enterprises put forth a compromise between the old and the new models of relations, introducing the institution of the employees' self-government and the 3 S rule (self-financing, self-dependence, self-government of enterprises). Although the solutions contained in the legislation promulgated after 1980 have not produced the effects commensurate with the original expectations, they introduced several important legal institutions, such as the right to strike; collective disputes or the employees' self-government. For the future reform of the labour law the above institutions remain of vital importance. However, it is also (necessary to add other elements, e. g. freedom of trade-unions (at present only 1 trade union organization per 1 factory is allowed, what is against ILO convention no. 87), more room for regulating matters connected with employment by contractual means, or equal treatment of socialized and non-socialized sectors. Generally speaking, the changes should go in the direction of a pluralistic and democratic model based on social agreements, self-governments of the employees and greater independence of employers due to a decreased influence of the State administration on their activities.
For a new model of the labour law